Aeshetics as a possibility for the study and understanding of the art of word – literature - Berisha, Labinot; Kastrati, Nexhmije (Edelweiss Applied Science and Technology, 2025)
Aesthetics, as a discipline, has evolved in parallel with the arts, reflecting an increasingly broad and interconnected range of concerns. It now encompasses a wide array of categories, concepts, and principles that continue to develop. During the European Enlightenment, art was regarded as a means of transmitting knowledge and promoting moral refinement. In contrast, Romantic aesthetics foregrounded imagination, creativity, and human freedom, thereby challenging Enlightenment ideals. Aesthetic thought has consistently been shaped by both individual and collective tastes, cultural contexts, and the ongoing development of artistic traditions and critical frameworks. Despite internal tensions and historical transformations, the field of aesthetics has expanded continually. Literature—particularly oral literature—cannot be fully understood outside of its cultural and performative context. Scholars such as Stefania Skwarczyńska and Ibrahim Rugova emphasize that while written literature is confined within the boundaries of the text, oral literature transcends those limits, engaging dynamically with its audience and environment. This paper further explores Aristotle’s Poetics, with particular attention to his conception of tragedy—not merely as the representation of suffering, but as a means of clarifying thought and evoking emotional insight. The contributions of additional scholars are examined through the lenses of interpretation, language, and perception. Ultimately, the study argues that the aesthetic experience of literature emerges through the interplay between the text and the reader’s context, individual sensibility, and capacity to engage with deeper meanings. In conclusion, aesthetics is essential for understanding the fundamental nature of literature, its artistic function, and its effect on the reader.